Gribašos 4-oji akmens amžiaus gyvenvietė - Grinevičiūtė, Giedrė (Archaeologia Lituana, 2002)
The site Gribaša 4 (Varėna district) is situated on the northeastern bank of the former Lake Duba (Fig. 1). The site represents some concentrations of artefacts that belong to different periods of the Stone Age from the Late Paleolithic to the Late Neolithic. It was found in 1998. In 1999–2000, a total area of 169.25 sq. m was excavated. 14,589 flint artefacts (Tab. 1) and 1,849 sherds of pots were discovered.The cultural layer was represented by 10–40 cm of thick yellowish sand. It was covered by a 10–36 cm thick layer pf top soil (Fig. 2.5). Three hearts were found (Figs. 2–4). It turned out that all remains belonged to 4 periods: the Late Paleolithic, the Late Mesolithic (LM), the Early Neolithic (EN) and the Late Neolithic (LN). Such a division of the excavated material (i.e., flint cores, retouched artefacts, some blades, ceramics) was based on typology, planigraphy (Figs. 4–6) and a little stratigraphy.Two tanged points (one was reworked into a burin), 6 double-platformed cores, several burins, and most of the 64 blades from double-platformed cores were attributed to the Late Paleolithic Swiderian culture (Fig. 7).The majority of the Late Mesolithic flint industry was characteristic of the late Mesolithic Nemunas (or Janislawice) culture. Features included highly developed blade and microburin techniques as well as some types of microliths (Figs. 11–12). Two types of blades were produced. Narrow microlithic blades of 8 mm in width and larger blades with wight of 10 or more mm were detached from single-platformed cores (Tab. 4). About 65% of the flint tools were made of blades (Tab. 3).Several microliths and some other flint tools were ascribed to the Early Neolithic (Figs. 11:13, 14, 17–18(?), 12:53–55, 60, 13:2, 5, 14–15). EN pottery sherds belonged to at least 5 pots (Fig. 16). The clay was tempered with plant fibre. Two vessels were ornamented with pits (Fig. 16:1,4), one was unornamented. These 3 pots could be related to the Early Neolithic Dubichay type. The other 2 pots contained fine organic temper. They represent another EN camp. One pot is especially characteristic of the EN Narva culture (Fig. 16:5). So, the inhabitants of the Narva culture reached territories of the EN Nemunas culture.One triangular arrowhead made from a blade (Fig. 18:1) and 4 pots ornamented with terraced stripes and pits (Figs. 17, 18:3) were attributed to the Middle Neolithic Nemunas culture. The vessels were tempered with either a mix of plant fibre and crushed quartzite or only with crushed quarzite.Twenty one flint artefacts (Fig. 18:2–16) were dated to the Late Neolithic. They were 7 triangular arrowheads made from flakes; 12 knives, one of which was polished; 2 scrapers. These artefacts probably were left by 2–3 LN camps.1,373 potsherds were attributed to the Late Neolithic. They belonged to at least 14 vessels. Four ceramic groups were classified by the temper:I. Pottery with mixed sand and small crushed quartzite (15% or 2 small vessels; see Fig. 19:2,4).II. Pottery with crushed mineral temper (75.1%).II.1. Two vessels (Fig. 21) whose decoration and shape resembled the pots of the Middle Neolithic Nemunas culture is Lysaja Gara type. However, the notches of the pots were stuck to the rim. This is characteristic of a Corded Ware Culture (called the CWC), Trciniec culture. No bottoms were found, so these vessels could have had point bottoms.II.2. Two concentrations (of 78 and 344 pottery sherds) were found on the site. They belonged to 2 thin-walled (0.5–0.7 cm) CWC vessels (Figs. 22–23). One pot was an amphora with 3–4 ears. Such ceramics are rather rare in South Lithuania.III. Pottery with an admixture of sand (+ silt?). (15.9% or at least 4 pots) (Fig. 24);In addition to the sand, 2 vessels contained some organic temper (silt?). It is possible that they contained a very small amount of tiny grog admixture.IV. Pottery with an admixture of grog and sand (+ silt?). (75% or at least 3 similar pots).In addition to sand and grog, all the vessels contained a small amount of organic temper (silt?) (Fig. 25). Such ceramics are especially characteristic of the CWC in South Lithuania. Analogous vessels were found in Karaviškės 6, Lynupis, Margiai 1 and other sites.Ceramics of the Late Neolithic were divided into 2 cultural groups. One of them shared a considerable number of features of the Middle Mesolithic Nemunas culture. This group contained vessels of the II.1 type and maybe the I type. Vessels of groups II.2, III, IV were ascribed to the Corded Ware Culture. Ceramics of types III and IV could be slightly earlier than the II.2 type.